FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK USIA 12-36 BULAN DI DESA CIJORO PASIR WILAYAH KERJA PUSKESMAS RANGKASBITUNG KABUPATEN LEBAK PROVINSI BANTEN TAHUN 2017 - Ariati Dewi; Marini Madiastuti; Sagita Yuliantini (Universitas Nasional, 2018)
Child health problems is one of the main problems in the field of health, until now diarrhoeal disease is still a global health problem, especially in developing countries. From year to year diarrhea remains one of the diseases that cause malnutrition and mortality in children. The incidence of childhood diarrhoeal disease in Cijoro Pasir Village Lebak Regency of Banten Province amounted to 182 (18%) toddlers. The purpose of this study is to determine what factors are associated with the incidence of diarrhea. The type of research is descriptive quantitative research with cross sectional approach. The population in the study was 1010 people and only 94 toddlers were sampled by accidental sampling.Univariate analysis showed that most of the toddlers had diarrhea (53,2%), with low birth weight (55,3%), less nutrition status (51,1%), non-exclusive breastfeeding (54.3%) and incomplete primary immunization (55.3%). Conclusion: There was a relationship between birth weight (p = 0.044), nutritional status (p = 0,000), exclusive breastfeeding (p = 0.026), and primary immunization (p = 0.015) with diarrhea occurrence in toddlers. Toddlers with less nutritional status is the most dominant variable having diarrhea chance with OR = 6,857. Suggestion: To prevent diarrhea occurrence in toddlers, puskesmas could provide the information or giving counseling and education about nutrition status, monitoring and measuring nutrition status and making improvement effort against diarrhea risk factors in toddlers.